Law no 6 of the year 2016 on amending some provisions of law 46/1978 on the realization of tax justice = قانون رقم 6 لسنة 2016 بتعديل بعض أحكام القانون رقم 46 لسنة 1978 بشأن تحقيق العدالة الضريبية - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Law no. 6 of the year 2016 on amending some provisions of law no. 46 of the year 1978 on the realization of tax justice قانون رقم 6 لسنة 2016 بتعديل بعض أحكام القانون رقم 46 لسة 1978 بشأن تحقيق العدالة الضريبية